Patches, Corridors, Matrix, Webs and Clouds. Expanding Richard TT Forman’s Land Mosaic Approach in the Medina of Tunis - Doherty, Gareth; Kotsoni, Areti (Ri-Vista. Research for landscape architecture, 2024)
This study proposes a framework for analyzing the medina of Tunis, based on Richard T.T. Forman’s theory of land mosaics. Departing from traditional preservationist methods, it views the Medina as a multifaceted landscape, integrating both tangible and intangible elements. Drawing from Félix Guattari’s concept of the three ecologies, the paper expands upon Forman’s model by introducing two additional categories: webs and clouds, to encompass the social and subjective aspects of the landscape. Through a literature review and landscape fieldwork, the study advocates for an integrative approach to analyzing the medina’s physical and intangible components. The resulting framework offers a landscape analysis tool applicable to other urban landscapes, moving beyond the taxidermy of urban/cultural conservation practices and considering marginalized communities affected by capitalism-driven heritage management and tourism. Such a perspective is integral in promoting social and ecological inclusivity and embedding sustainable practices, particularly in response to the pressing challenges of climate change. Ultimately, this approach would help the contemporary landscape project succeed in “grounding new narratives and topologies” of “re-signification” of other historic urban areas and medinas across North Africa.